Country or leader?: political change and UN General Assembly voting - Dreher, Axel; Jensen, Nathan M. (European journal of political economy, 2013)
We investigate empirically changes in voting in the United Nations General Assembly consequent to leader turnovers over the 1985-2008 period and find evidence that governments with new rulers are more supportive of the United States on important votes. We consider the explanations that might underlie our empirical result, including material gain and ethical motivations. In contrast to our findings on key votes, our results show that voting on non-key votes in the General Assembly does not robustly shift towards the U.S. following leader change. We therefore conclude that material gain is the most likely reason for the observed pattern.